Evaluation of castor landraces collected from N-W Rajasthan as noval genetic resources for breeding: Evaluation of castor landraces collected from N-W Rajasthan as noval genetic resources for breeding - J JAWAHAR LAL; K ANJANI (Journal of Oilseeds Research, 2023)
An exploration was conducted in North-Western Rajasthan state and a total of 114 castor germplasm lines were collected from seven districts. Most of the accessions were tall in plant height. Variability for different traits viz., plant height (50-275 cm), node number (10-35), total length of primary spike (16-60 cm), length of primary spike covered by capsules (6-60 cm), 100 seed weight (7.1-53 g), total seed yield (23-416 g/plant)among the collections were very high. These 114 genotypes were grouped into 11 clusters using D2 analysis. Among the 11 clusters studied, plant height contributed highest towards genetic divergence (45.8%) followed by total seed yield/plant (36.4%). Principal component (PCA) analysis revealed that first three PC axes explained 64.7% of the total multivariate variation while the first five PC axes explaining 81.7%. Among these diverse germplasm collections few promising accessions identified for node number RG-3840 (10), RG-3841 (11), 100-seed weight, RG-3832 (53.2g), RG-3839 (52.6 g), RG-3831(49.5 g), seed yield/plant, RG-3851-(416 g), RG-3860 (305 g) and RG-3895 (238 g). These landraces were found to be potential source of genetic diversity to castor repository.